Characterization of UTI associated with health - Arias Arango, Angela Maria; Valderrama Maya, Monica Patricia; Parra Pérez, Doris Milena; Marin Zuluaga, Juan Ignacio; Mazo Monsalve, Luz Maria; Montoya Zapata, Claudia Patricia (Investigación y Educación en Enfermería, 2025)
Objective. To describe epidemiological, microbiological and clinical characteristics of patients with health care associated urinary tract infection (UTI) in the adult hospitalization services in a fourth level attention hospital in the city of Medellin (Colombia) between 2007 and 2009. Methodology. Descriptive study. 239 clinical histories of patients with health care associiated UTI diagnosis registered in the Infection Prevention Committee were studied. Results. 269 episodes of health care associated UTI were analyzed. The average age of the patients was 56±19.2 years. 55.3% of the infections were in women. 69.1% had permanent catheter at the moment of the diagnosis or 7 days previous to it. In 12.4% the indication for the catheter wasn’t appropriate. 308 microorganisms were isolated in the studied cases, being the most frequent ones Escherichia coli (42.2%) and Klebsiella pneumoniae (23.4%). The main complications were secondary bacteremia (9.2%) and septic shock (0.8%). Conclusion. In an important percentage of patients the evaluation of the indication for putting the catheter wasn’t shown, which can influence the growth of the risk of acquiring urinary infections increasing the use of antibiotics which contributes to an increase in bacteria resistance and health care costs.